Esophageal Squamous Cell Carcinoma Presenting as a Subepithelial Tumor - Soon Young Kim; Sang Kil Lee; Hyang Joo Ryu (The Korean Journal of Helicobacter and Upper Gastrointestinal Research)
Esophageal squamous cell carcinoma (ESCC) presenting as subepithelial tumor-like growth is a very rare form of the disease. We report a case of primary ESCC with intramural growth, covered with normal esophageal epithelium. The patient was initially referred due to a subepithelial tumor at the mid-esophagus, butendoscopic ultrasonography revealed a heterogeneously hypoechoic mass, which disrupted the structure of the muscularis propria. An endoscopic submucosal dissection was performed for accurate diagnosis, and the lesion was diagnosed histopathologically as moderately differentiated squamous cell carcinoma. Computed tomography revealed an enlarged left upper paratracheal lymph node, which showed increased uptake on positron emission tomography. The patient underwent subtotal esophagectomy with total mediastinal lymphadenectomy and adjuvant chemotherapy. Primary ESCC with intramural growth is extremely rare. For accurate diagnosis, when there is a high index of suspicion, additional investigations such as endoscopic ultrasonography or diagnostic endoscopic submucosal dissection might be needed.